Biodiversity conservation in human-modified landscapes of Mesoamerica : past, present and future - Chazdon, Robin L (2010)
Mesoamerica provides a unique context for biodiversity conservation in managed landscapes because of its geography, history of human intervention, and present conservation and development initiatives. The long and narrow form of the Mesoamerican landmass, and its division by a central mountain range, has served as both a bridge and a barrier. Conservation efforts in Mesoamerica are unique for the emphasis they place on regional connectivity through the Mesoamerican Biological Corridor and on biodiversity conservation in managed landscapes. The emphasis on conservation in agricultural systems has fostered innovations in payment for ecosystem services, and provides novel insights on the functional role that biodiversity plays in the provisioning of ecosystem services. The increasing rate of economic development in the region and the advent of new payment for ecosystem service schemes have provided new opportunities for forest regeneration and restoration. However, the small scale of private landholdings and the diversity of land uses featured in the region, while contributing to biodiversity conservation due to their structural and floristic complexity, present challenges for biodiversity monitoring and management.